2008
DOI: 10.1037/1099-9809.14.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Examining cultural socialization within African American and European American households.

Abstract: This preliminary study explored the cultural socialization processes of 227 African American and European American parents of elementary schoolchildren. The Cultural Value Socialization Scales (K. M. Tyler, A. W. Boykin, C. M. Boelter, & M. L. Dillihunt, 2005) were used to garner parents' reports of their cultural value socialization activities at home. The scales contained written vignettes depicting persons involved in activity that reflected a specific cultural value. Ethnocultural values examined were comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Moreover, little research has been conducted to examine how adolescents’ cultural values might be shaped/influenced by social behaviors, such as prosocial behavior. The culturally guided social interaction processes including prosocial behavior toward powerful people likely serve as an important socialization agent of children’s cultural value development [11]. Thus we tried to extend the existing literature by examining the longitudinal and bidirectional relations between adolescents’ power distance value and prosocial behavior toward powerful people in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, little research has been conducted to examine how adolescents’ cultural values might be shaped/influenced by social behaviors, such as prosocial behavior. The culturally guided social interaction processes including prosocial behavior toward powerful people likely serve as an important socialization agent of children’s cultural value development [11]. Thus we tried to extend the existing literature by examining the longitudinal and bidirectional relations between adolescents’ power distance value and prosocial behavior toward powerful people in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural socialization refers to the developmental processes through which children learn about histories and traditions of a culture, acquire cultural beliefs and values, and develop positive attitudes toward that culture (Hughes et al, 2006; Romero, Cuéllar, & Roberts, 2000; Tyler et al, 2008). The existing literature has examined cultural socialization almost exclusively as parents’ efforts to teach and maintain their heritage culture for their children (e.g., cultural socialization in Hughes et al, 2006; ethnic socialization in Umaña-Taylor, Alfaro, Bámaca, & Guimond, 2009, enculturation in Lee, Grotevant, Hellerstedt, & Gunnar, 2006), yet prior work also indicates that parents socialize their children toward the mainstream culture (e.g., Romero et al, 2000; Tyler et al, 2008). To capture culture socialization in a more comprehensive manner, the present study examines socialization practices toward both one’s heritage culture and the mainstream American culture.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to one’s heritage culture, parents also teach children about the mainstream American culture in both overt and covert ways. Prior work has documented parents’ efforts to promote knowledge and preferences of the mainstream group (Romero, Cuéllar, & Roberts, 2000), to encourage children to be involved in the mainstream culture (Stevenson et al, 2002), and to convey beliefs and values of the mainstream American culture (Tyler et al, 2008). Our own work using a mixed-methods approach demonstrated that parents actively stress the importance of learning about the mainstream American culture, teach children about the values and practices of the mainstream culture, and implicitly practice mainstream cultural socialization by involving adolescents in events and activities that represent the mainstream culture (Y.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the cultural values of African Americans include a strong achievement orientation, as well as endorsement of effort and hard work, as a means of upward mobility (Bowman & Howard, 1985;Hill, 1972;Hughes, 2003;Hughes et al, 2006;Nobles & Goddard, 1984). These values, like other Afrocultural values (see Tyler et al, 2008) have been generationally transmitted from parent to child through the process of racial socialization. This may shape an adolescent's view of intelligence as varying with hard work, thus translating into socialization around education.…”
Section: Discussionmentioning
confidence: 99%